Community Empowerment in The Economic Field of Fish Farmers in The Corporate Social Responsibility Program - Rudy Kurniawan; Ravik Karsidi; Sapja Anantanyu; Sugihardjo Sugihardjo (AIBPM Publisher, 2022)
ABSTRACT This study aims to describe the concept of Corporate Social Responsibility (CSR) in PT. Multi Dimensi Kreasi (MDK), reviewing the implementation of PT. MDK's CSR program, formulating a model for empowering fish farmers and assessing the success of empowering fish farmers in the Bokesan, Sindumartani Village, Sleman, Yogyakarta. The research method is qualitative. The sampling technique used was purposive sampling, snowball sampling, and Forum Group Discussion (FGD). Data collection techniques consist of interviews, observation, and documentation. The data validation technique used is triangulation. The data analysis technique uses an interactive model. The results of the study concluded that the CSR in PT. MDK is done by applying the innovation concept of Micro Bubble Generator (MBG), the CSR Implementation is carried out with the principles of empowerment, and the empowerment model, namely Intensification of aquaculture with MBG innovation, Stages of empowerment, including awareness, capacity, and empowerment, Community empowerment in the economic sector through PT. MDK's CSR program for fish farmers is quite successful.Keywords: Community Empowerment, Economy, Corporate Social Responsibility, Micro Bubble Generator.